Guatemala, an Early Spectrum Management Reformer - Marino Garcia, Jose (World Bank, Washington, DC, 2016)
There are powerful arguments for regulating spectrum allocations as a scarce resource. These stem from the likelihood of interference between radio communication services, economies of scale, externalities linked to some of the commercial services using the spectrum, the existence of services which may be considered pure public goods, along with conditioning factors linked to the legacy usage of spectrum. While the concept of best practice in spectrum management regime remains controversial, the case of Guatemala is a perfect ‘experiment’ to discern the effect of policies where the market is afforded a more important role in the allocation of frequencies.